First record of Lucilia bufonivora Moniez, 1876 (Diptera: Calliphoridae) from North America and key to North American species of the L. bufonivora species group - Tantawi, Tarek I.; Whitworth, Terry (Zootaxa, 2014)
The obligate anuran myiasis blow fly Lucilia bufonivora Moniez is reported from North America for the first time. The L. bufonivora species group is defined on the basis of the aedeagus and the history and biology of the North American species (L. bufonivora, L. elongata Shannon and L. silvarum (Meigen)) are discussed. A key is provided to separate the three North American species of this group. The North American species L. thatuna Shannon, a member of the L. sericata (Meigen) species group, is also treated because it is likely a parasite of anurans and is poorly known. The male abdominal sternites, aedeagus (L. elongata only), pregonites, postgonites, bacilliform sclerites, ejaculatory sclerites, and female ovipositors and spermathecae of L. elongata and L. thatuna are illustrated for the first time.